Synthesis, Characterization, and Antimicrobial Properties of New 1,3,4‐Thiadiazoles Derived from Azo Dyes - Gür, Mahmut (Wiley, 2019)
Some new 1,3,4‐thiadiazoles derived from azo dyes were synthesized. Two different synthesis methods were used for these compounds: Esters pertaining to the azo dyes were converted into 1,3,4‐thiadiazoles, or benzothiazole ester derivatives were converted to 1,3,4‐thiadiazoles followed by the synthesis of azo dye derivatives. The desired products were successfully obtained using the latter method. The molecular structures of these compounds were characterized using spectroscopic methods such as FTIR, 1H NMR, 13C NMR, and elemental analysis. Furthermore, antimicrobial activity was studied for the synthesized compounds. Compound 3e exhibited antimicrobial activity against three different microorganisms. Compounds 3a, 3b, and 3d had activity against two different microorganisms, while compound 3c showed activity against only one microorganism.